Limewashing paintings in Alentejo urban heritage: pigment characterization and differentiation by WDXRF and XRD - Gil, M. (2012)
Pigments used in traditional limewashing paintings in Alentejo urban Heritage are inorganic materials and can be grouped into four categories: a) reds – red ochre (from terras rossas, red schists and iron ore deposits weathering), almagres,terra roxa (natural processed red ochres) and synthetic red iron oxides; b) yellows – yellow ochre (from schists and iron ore deposits), processed natural ochres, yellow iron synthetic oxides,c) blacks – black earths and black iron synthetic oxides and d) blues – artificial ultramarine. The present work proposes to characterize natural, natural processed and synthetic pigments by comparing phase and elemental compositions. The results reveal differences in Fe, Si, K and Al total content according to their origin and fabrication process and reveal intentional addition of white charges like carbonates. Elements like Zr, Ti, Cr, Mn, Ca and Zn are present in all categories. Under optical microscopy, some samples of processed natural pigments do not exhibit optical activity, thus revealing mixtures with synthetic pigments, while natural pigments present a strong birefringence colorless due to optically active minerals.